Formação continuada de professores: possibilidades e perspectivas para a construção da autonomia - Fripp, Leila de Fátima Haubert (Universidade do Vale do Rio do Sinos, 2006)
This work has rootses in the history of my life. Remembering stongest moments in my school life, while student and later on for the exercise of my occupation, I tried to revive this trajectory reconstructing last time, for, then to understand the present and to contemplate on the future. My objective is that the educational ones find sense in its occupation, understanding the importance and the need of they form her continually for the improvement of its educational practice. The research is centered in a qualitative point, and we looked for to understand what the educational ones thinks concerning the continuous formation, including them know built by them, the autonomy possibility and their profession. The reference of this work is Paulo Freire's work, that makes her present in all the chapters of the study. I also fell back upon Terezinha Rivers' contributions, Carlos Estevão, Maria Isabel of Cunha, Antonio Nóvoa, Osório Marques, Maurice Tardif, José Contreras, Mariano Engueta, Carlos Brandão, Mário Mell
Keywords: autonomia; profissionalidade; saberes docentes; formação continuada; autonomy; profession; you know educational; continuous formation; Ciências Humanas